2008
DOI: 10.1128/iai.01515-07
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Granulomas Are Hypoxic in Guinea Pigs, Rabbits, and Nonhuman Primates

Abstract: Understanding the physical characteristics of the local microenvironment in which Mycobacterium tuberculosis resides is an important goal that may allow the targeting of metabolic processes to shorten drug regimens. Pimonidazole hydrochloride (Hypoxyprobe) is an imaging agent that is bioreductively activated only under hypoxic conditions in mammalian tissue. We employed this probe to evaluate the oxygen tension in tuberculous granulomas in four animal models of disease: mouse, guinea pig, rabbit, and nonhuman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
538
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 575 publications
(576 citation statements)
references
References 43 publications
26
538
1
1
Order By: Relevance
“…Indeed, transcriptional analysis of M. tuberculosis during infection of macrophages indicates the organism adapts to a reduced oxygen environment (21), and improved growth of Chlamydia pneumoniae is observed under low oxygen conditions (22). Like M. tuberculosis, C. burnetii can occupy tissue granulomas (23), a defined low oxygen environment (24). Mammalian cell intracellular oxygen tension can be significantly lower than the extracellular oxygen tension (25).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, transcriptional analysis of M. tuberculosis during infection of macrophages indicates the organism adapts to a reduced oxygen environment (21), and improved growth of Chlamydia pneumoniae is observed under low oxygen conditions (22). Like M. tuberculosis, C. burnetii can occupy tissue granulomas (23), a defined low oxygen environment (24). Mammalian cell intracellular oxygen tension can be significantly lower than the extracellular oxygen tension (25).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that caseous granulomas, a common type seen in human TB, are hypoxic in various animal models (guinea pigs, rabbits, and nonhuman primates), whereas nonnecrotizing granulomas (primarily composed of macrophages with sparse lymphocytes) are not hypoxic (11). Murine granulomas are less-organized collections of macrophages and lymphocytes without central caseous necrosis and are generally not hypoxic (11,13). M. tuberculosis grown under low-oxygen conditions is not susceptible to INH (14).…”
mentioning
confidence: 99%
“…In this context, the ESAT-6 response could be used to predict drug efficacy, as it precedes a significant decrease in the numbers of lung CFU. While the TB mouse model is by far the most convenient and widespread experimental tool, mice do not develop organized, necrotic, and hypoxic lesions (6,35,37). It is only recently that the rat has been investigated as a potentially predictive model of TB infection (4, 34).…”
Section: Discussionmentioning
confidence: 99%